1983
DOI: 10.1111/j.1348-0421.1983.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Macrophage DNA Synthesis by Immunomodulators

Abstract: Oil-induced guinea pig peritoneal exudate macrophages were found to incorporate actively [3H]thymidine without any tissue fluids such as conditioned medium, lymphokines or inflammatory tissue exudates. The [3H]thymidine incorporation was markedly suppressed by macrophage stimulants such as muramyl dipeptide (MDP) or bacterial lipopolysaccharide (LPS), while glucosamine incorporation was simultaneously increased by these stimulants. The degree of suppression of thymidine incorporation depended on the cell densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…The proliferative activity of MDMs was not significantly modified (P Ͼ 0.05) by treatment with Murabutide (1,123 Ϯ 212 on day 2 and 1,150 Ϯ 207 on day 6). This is in contrast to the effects of other immunomodulators, including LPS, which have been reported to inhibit macrophage DNA synthesis (42).…”
Section: Resultscontrasting
confidence: 42%
“…The proliferative activity of MDMs was not significantly modified (P Ͼ 0.05) by treatment with Murabutide (1,123 Ϯ 212 on day 2 and 1,150 Ϯ 207 on day 6). This is in contrast to the effects of other immunomodulators, including LPS, which have been reported to inhibit macrophage DNA synthesis (42).…”
Section: Resultscontrasting
confidence: 42%
“…We recently found that DNA replication of macrophages was markedly inhibited when the macrophages were activated by MDP (22). This fact suggests that MDP stimulates macrophages to differentiate into epithelioid cells (this possibility will be discussed in more detail separately).…”
Section: Discussionmentioning
confidence: 98%